ESG as protection against downside risk - Roman Kräussl; Tobi Oladiran; Denitsa Stefanova (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
We examine whether the uncertainty related to environmental, social, and governance (ESG) regulation developments is reflected in asset prices. We proxy the sensitivity of firms to ESG regulation uncertainty by the disparity across the components of their ESG ratings. Firms with high ESG disparity have a higher option-implied cost of protection against downside tail risk. The impact of the misalignment across the different dimensions of the ESG score is distinct from that of ESG score level itself. Aggregate downside risk bears a negative price for firms with low ESG disparity.
Keywords: G12; G18; G32; 330; ESG; rating; downside risk; options; regulation; risk premium